Female terrorism in America: past and current perspectives - Matusitz, Jonathan (Contemporary terrorism studies, 2021)
Introduction -- Definitions and Background -- Theoretical Perspectives -- Female Terrorism in Left-Wing American Organizations -- Female Puerto Rican Terrorism in America -- Female Terrorism in Right-Wing American Organizations -- Roles in Female Terrorism: From Leadership to More Passive Positions -- Radicalization to Terrorism -- Depictions in the Media -- Motivations for Joining Terrorist Organizations -- Muslim Female Terrorists in America -- The Influence of Social Media -- The Inflammatory Rhetoric of Female Terrorists -- Conclusions, Implications, and Solutions.